2011
DOI: 10.3340/jkns.2011.50.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Tarlov Cyst Following Spontaneous Subarachnoid Hemorrhage

Abstract: A 75-year-old woman was transferred to the emergency room, complaining of severe headache of sudden onset, low back pain, nausea, and dizziness. She was alert and oriented. She had signs of meningeal irritation, but the neurological examination was otherwise normal. Brain CT revealed SAH in the right Sylvian fissure and basal cistern. Three-dimensional brain CT angiography showed a right middle cerebral artery aneurysm. Emergent craniotomy via right-sided pterional approach without installation of lumbar cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The patient relieved from pain after CT-guided aspiration of the cyst, and 1 cc of old blood was aspirated from the cysts, which proved the accumulation of the SAH into the cysts. 10) In our case, the perineurial cysts presented symptoms 4 days after the onset of the SAH. Assuming that it takes a few days for the accumulation of the SAH into the sacral cysts to become symptomatic, this time lag appears to be reasonable.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The patient relieved from pain after CT-guided aspiration of the cyst, and 1 cc of old blood was aspirated from the cysts, which proved the accumulation of the SAH into the cysts. 10) In our case, the perineurial cysts presented symptoms 4 days after the onset of the SAH. Assuming that it takes a few days for the accumulation of the SAH into the sacral cysts to become symptomatic, this time lag appears to be reasonable.…”
Section: Discussionmentioning
confidence: 49%
“…To the best of our knowledge, there is only one previous report of symptomatic perineurial cysts related to the aneurysmal SAH, 10) and our case is the first report of those triggered by NAPH. In the previous report, the patient complained of worsening pain in the lumbosacral, buttock, and the posterior aspect of the right thigh, following neck clipping of ruptured aneurysm.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Kong et al reported a case of a symptomatic perineural cyst secondary to spontaneous haemorrhage into the subarachnoid space 17. The authors suggested that the haemorrhage resulted in increased hydrostatic pressure of CSF, which leads to the infiltration of CSF and haemorrhage into a pre-existing perineural cyst.…”
Section: Discussionmentioning
confidence: 99%
“…They are found most often in the sacral roots 1 and, rarely, cause symptoms related to nerve root compression. 2 The literature is limited when it comes to the management of these ruptured cysts.…”
Section: To the Editormentioning
confidence: 99%